2016
DOI: 10.1364/ao.55.005033
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion engineering in nonlinear soft glass photonic crystal fibers infiltrated with liquids

Abstract: We present a numerical study of the dispersion characteristic modification of nonlinear photonic crystal fibers infiltrated with liquids. A photonic crystal fiber based on the soft glass PBG-08, infiltrated with 17 different organic solvents, is proposed. The glass has a light transmission window in the visible-mid-IR range of 0.4-5 μm and has a higher refractive index than fused silica, which provides high contrast between the fiber structure and the liquids. A fiber with air holes is designed and then develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…1, we have considered nonlinear Schrödinger equation (NLSE). Other researchers demonstrated that the numerical results calculated by this model are close to the experimental results [12], [23][24][25]. Evolution of an optical pulse, having a slowly varying electric field amplitude represented by envelope function A(z, t) defined by GNLSE [24]:…”
Section: Mathematical Backgroundsupporting
confidence: 71%
See 2 more Smart Citations
“…1, we have considered nonlinear Schrödinger equation (NLSE). Other researchers demonstrated that the numerical results calculated by this model are close to the experimental results [12], [23][24][25]. Evolution of an optical pulse, having a slowly varying electric field amplitude represented by envelope function A(z, t) defined by GNLSE [24]:…”
Section: Mathematical Backgroundsupporting
confidence: 71%
“…One of these approaches is changing the core diameters. Reducing the core diameter has some limitations: first, PCF fabrication is hard to do, second, while propagating in fibers, short wavelengths can pass through small core cross section area but long wavelengths that require larger effective cross-sectional area cannot be confined in the core and they might enter the cladding [24]. This will be considered as a leakage loss because it is not accessible anymore.…”
Section: Pcf Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The main properties of PCF influencing on the application ©2020 Vietnam Academy of Science and Technology fields are the effective refractive index, effective mode area, dispersion, and confinement loss. Up to now, there is a lot of works, theoretical as well as experimental, that investigated the effective refractive index [9][10][11], guiding mechanism of light in photonic crystal fiber [12], effective mode area [13,14], dispersion [15][16][17][18][19][20] and confinement loss [21][22][23] and improved them by infiltration on air-holes with liquids for specific applications. In recent years, PCFs with air holes have been infiltrated with liquids having different refractive index and higher nonlinearity on the cladding or the core of photonic crystals fiber as designing a dual-core PCF coupler [24], D-glucose sensor using PCF [25], dispersion engineering of photonic crystal fibers by means of fluidic infiltration [26], liquid-filled simplified hollow-core PCF [27].…”
Section: Introductionmentioning
confidence: 99%
“…Application of liquids with various refractive indexes allow for the modification of dispersion properties of the fiber without changing its geometrical parameters, which seems to be very practical (Pniewski et al 2016). Moreover fiber properties can be further dynamically modified by means of temperature and pressure adjustment, since liquids are much more sensitive to these parameters than glass itself.…”
Section: Introductionmentioning
confidence: 99%